Recent developments in synthesis and characterisation of graphene oxide modified with deep eutectic solvents for dispersive and magnetic solid-phase extractions - Emmanuel Ibukun, Aduloju; Yahaya, Noorfatimah; Husaini Mohamed, Ahmad; Semail, Nadhiratul-Farihin; Abd Hamid, Muhammad Ariffuddin; Nadhirah Mohamad Zain, Nur; Anuar Kamaruddin, Mohammad; Hong Loh, Saw; Kamaruzaman, Sazlinda (Elsevier, 2024)
Over the years, recent advancements have provided new insights into the functionalisation and synthesis of graphene oxide-based materials for sample preparation applications, utilising deep eutectic solvents (DESs). The demand for efficient, selective, innovative, and simple sample preparation of contaminants and pollutants from various matrices has rapidly focused on dispersive and magnetic solid-phase extraction. This study summarises the use of graphene oxide and reduced graphene materials in DES-based synthesis and functionalisation, along with their physicochemical characteristics and applications in dispersive and magnetic solid-phase extraction. The majority of DESs have demonstrated significant enhancements in the extraction of targeted analytes by increasing the effective surface area for active sites and introducing desired functionalities. Upon reviewing the existing literature, it was observed that DESs were functionalised either during or after the production of graphene materials. The findings highlight that dispersive and magnetic solid-phase extraction, incorporated with DES-functionalised graphene adsorbents, offer superior advantages for routine sample pretreatment of analytes, leading to enhanced analytical performance.